The Impact of Productive Zakat Program on the Economy of Zakat Recipients: Study in Baznas Surakarta - Azhar Alam; Deviana Sari; Lukmanul Hakim (Journal of Islamic Economics and Finance Studies, 2022)
This study aims to reveal the impact of productive zakat of Baznas Surakarta on the economy of zakat recipients. The research of impact that is based on the perceptions of zakat recipients is fundamental so that Baznas Surakarta can evaluate some program deficiencies and determine whether effective zakat programs help the welfare of zakat recipients. This study is descriptive qualitative research by conducting in-depth interviews with Baznas Surakarta officials and ten productive zakat recipients. The results of this study indicate that in the view of zakat recipients, the effective zakat program has improved the recipients' economy, and the majority of their businesses have been able to develop. However, to develop a business, the tenacity of zakat recipients is required to manage their business.On the other hand, the form of supervision carried out by Baznas Surakarta still needs to be improved by providing capital without training. Furthermore, Baznas Surakarta has yet to confirm whether the zakat funds given to zakat recipients are used optimally. This study recommends the importance of supervision in the distribution of zakat in the form of productive business funding.  Penelitian ini bertujuan untuk mengungkapkan dampak zakat produktif dari Baznas Surakarta terhadap kondisi ekonomi penerima zakat. Penelitian dampak berdasarkan persepsi penerima zakat sangat penting agar Baznas Surakarta dapat memperbaiki kekurangan program dan mengetahui apakah program zakat produktif membantu mensejahterakan kehidupan penerima zakat. Penelitian ini merupakan penelitian kualitatif deskriptif dengan melakukan wawancara mendalam terhadap petugas Baznas Surakarta dan sepuluh penerima zakat produktif. Hasil penelitian ini menunjukkan bahwa dalam pandangan penerima zakat program zakat produktif telah meningkatkan perekonomian mustahiq dan mayoritas bisnis mereka mampu berkembang. Namun demikian, untuk mengembangkan usaha diperlukan keuletan penerima zakat dan mampu mengelola usahanya. Di sisi lain, bentuk pengawasan yang dilakukan oleh Baznas Surakarta masih belum optimal dengan hanya memberikan modal tanpa pelatihan. Baznas Surakarta belum dapat memastikan apakah dana zakat yang diberikan kepada penerima zakat digunakan secara maksimal. Penelitian ini merekomendasikan pentingnya supervisi dalam pendistribusian zakat dalam bentuk pendanaan usaha produktif.